A utilização de tecnologias educacionais em atividades extracurriculares na política pública de ensino em tempo integral - Fernandes, Carlos Eduardo Lima (2024)
In Full-Time Schools (FTE), students have longer curricular hours, and the long time spent in the classroom requires the establishment of different teaching strategies by teachers. The Brazilian Law nº 14.180/21 establishes the right to access to the internet, to quality educational resources and to promoting access to innovation and technology, which in the context of FTE’s, becomes an even more concrete normative dictate, given the best structure that these schools offer. Therefore, this work aimed to analyze the application of a teaching methodology using educational technologies for extracurricular activities in FTE’s. To this end, a survey of the teaching strategies used by teachers was carried out, through semi-structured interviews (Bardin, 1977). Next, a pedagogical kit was developed and tested, in an extracurricular activity called “Young Lawyer Club”, following the intervention methodology (Damiani et al., 2013). And finally, the effects of the methodology developed were analyzed, through the application of a questionnaire to the students, with parameters on an agreement scale (Likert, 1932). The subjects consisted of 12 (twelve) students, between 14 and 16 years old, and 03 (three) teachers, from the final years of Elementary School at an FTE in the city of Fortaleza/CE. The product of this research consists of a pedagogical kit for the extracurricular activity “Young Lawyer Club”, aimed at teaching introductory concepts of Criminal Law, in order to achieve the ethical and moral training of teenagers, and reduce local crime rates. The kit contains: 1 (one) lesson plan template, 1 (one) e-mail address, 1 (one) Instagram account, 1 (one) YouTube channel, 1 (one) website, 1 (one) illustrated e-book and 1 (one) script for conducting a simulated Jury. It was possible to identify a wide range of educational technologies used by teachers as didactic strategies in teaching. Using the kit made students remain more focused and involved in the subject. It was noticed that a good physical structure and the continued training of teachers are fundamental factors for the implementation of public policy. And it is important that future research monitors and evaluates public policy on full-time education, as well as the use of educational technologies, in order to propose solutions and readjust routes to better conduct these initiatives.